DEKONSTRUKSI CERITA DARMAWULAN-MENAK JINGGO DI KABUPATEN BANYUWANGI - Miskawi; Maulana Yusuf Arrasuly; Warto (Universitas Negeri Surabaya, 2025)
The Damarwulan–Minakjinggo story is part of the traditional Langendriyan art heritage and developed in Banyuwangi. This story depicts the conflict between Damarwulan and Minakjinggo. Historically, this story was used by the Mataram Sultanate to build political legitimacy by depicting Minakjinggo as rebels, while the Dutch adapted the narrative to stigmatize the Blambangan community. This study aims to examine the origins, transformations, and impacts of this performance in a political and cultural context, using historical methods with a deconstruction approach from Derrida. The discussion highlights how this story was transformed into a tool for political legitimacy, as well as how the Banyuwangi community reconstructed the story to strengthen local identity. The implications of this study indicate that the transformation of the Damarwulan-Minakjinggo story strengthens local identity and makes art a means of resistance to dominant narratives. In conclusion, this story reflects how art and historical narratives can adapt to social and political changes, and enrich understanding of cultural identity that is relevant to modern values.